Supply chain management and performance in the Portuguese furniture industry - Patrício, Pedro Miguel Rodrigues (2016)
The purpose of the thesis is to investigate whether companies that implement supply chain management (SCM) practices and the impact on performance. This thesis adds to the existing literature by investigating the influence of implementing SCM practices, having the focus on the company and it’s practices rather than on the external interveners. The study was conducted by surveying a questionnaire to the Portuguese furniture manufacturing companies and comparing that information with financial data to assess the impact of these practices on the companies’ performance. With this thesis it was possible to conclude that the impact on companies’ performance by having SCM practices is positive.